2013
DOI: 10.1016/j.eururo.2012.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Does Comorbidity Influence the Risk of Myocardial Infarction or Diabetes During Androgen-Deprivation Therapy for Prostate Cancer?

Abstract: Background Androgen deprivation therapy for prostate cancer is associated with cardiovascular disease and diabetes. Some data suggest that men with certain conditions may be more susceptible to developing cardiovascular disease than others. Objective Assess whether the risk of myocardial infarction or diabetes during androgen deprivation therapy is modified by specific baseline comorbidities. Design, Settings and Participants Population-based observational study of 185,106 U.S. men aged ≥66 years diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 27 publications
3
58
0
2
Order By: Relevance
“…Two studies included only men aged 66 years or older (Keating et al 2006, Alibhai et al 2009) while in the third cohort over 40% of the cohort were younger than 66 years . The risk of developing diabetes with ADT was independent of known risk factors (Keating et al 2013).…”
Section: Insulin Resistance and Type 2 Diabetes Mellitusmentioning
confidence: 91%
“…Two studies included only men aged 66 years or older (Keating et al 2006, Alibhai et al 2009) while in the third cohort over 40% of the cohort were younger than 66 years . The risk of developing diabetes with ADT was independent of known risk factors (Keating et al 2013).…”
Section: Insulin Resistance and Type 2 Diabetes Mellitusmentioning
confidence: 91%
“…Limitations include the lack of information on lifestyle factors and exact indications for palliative radiotherapy, and there may still be residual confounding, which could not be accounted for [13,32,33]. The selected proxies of disease progression, namely TURP, palliative radiotherapy and nephrostomy, may correspond to local or metastatic disease progression, but have been shown to be consistently associated with an increased risk of morbidity in this cohort [13].…”
Section: Discussionmentioning
confidence: 99%
“…65 A retrospective analysis, however, using data from the Cancer of the Prostate Strategic Urologic Research Endeavor (CaPSURE) and including men with prostate cancer treated with radical prostatectomy followed or not with ADT found a significant correlation of ADT with increased CV mortality, but only among patients over 65 years old (p=0.002). 66 Furthermore, a recent meta-analysis of randomized controlled trials and observational studies showed that antiandrogen was associated with a 30% decreased risk for myocardial infarction compared to GnRH agonists, while combined androgen blockade was associated with a 10% increased risk for stroke when compared to antiandrogen.…”
Section: Adt and The Risk Of Cardiovascular Diseasementioning
confidence: 99%